Pengaruh Penambahan Kulit Singkong Terhadap Kualitas Pupuk Organik Cair dari Limbah Buah yang Diaplikasikan pada Tanaman Cabai Merah Keriting (Capsicum Annum L) - Ika Pratiwi; Lulu Indah Kusumaningrum; Ieling Dikya Akriz; Dini Ocktaviani; Fatih Armandika; Duta Muwafaq (Politeknik Negeri Cilacap, 2023)
Every day the traditional market produces garbage from rotting fruit. According to the Ministry of Environment and Forestry (KLHK), the incidence of waste produced in Indonesia is 23 million tons / year and 22.3% comes from traditional marketwaste. Fruit waste can be utilized into Organic Fertilizer Cwater (POC) in order to have a selling value and not pollute the environment. In thepreviousstudy, the additional material used was cassava and only measured the nutrient levels of Liquid Organic Fertilizer formed without application to the plant,so that in penelitian ini wasdone the addition of cassava peel in the manufacture of liquid organic fertilizers and its effectonthe growth of curly red chili plants. The method used is fermentation inside the reactor equipped with a temperature stabilizedbottle. Processing is carried out anaerobically for 2 weeks with a variety of additional materials in one of the reactors, namely the addition of cassava peel. The parameters to be observed are pH levels, viscosity, plant height and number of leaves. Based on the results of measurements of pH levels before fermentation and after fermentation, the pH of liquid organic fertilizers with the addition of cassava peel from 5 to 3 and pH of Liquid Organic Fertilizer without the addition of cassava peel from 6 to 4. The results of measurement of the viscosity level of Liquid Organic Fertilizer without cassava peel 9,544x10-4 N. s/m2 while liquid organic fertilizer without cassava peel 7,858x10-4 N. s/m2. This means that liquid organic fertilizer without cassava peel is more easily absorbed by the soil because the viscosity value is lower and close to the water viscosity value of7,768x10-4 N. s/m2. The application of Liquid Organic Fertilizer to the curly red chili plant canget a maximum result of its effect by Liquid Organic Fertilizer without the addition of cassava peel.